2021
DOI: 10.1080/08959420.2020.1851349
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Staff Retention and English Care Home Quality

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…136 However, there is only a small amount of evidence for England as to the effects that staff and their employment conditions have on the quality of care homes. 148,149 This study sought to assess whether or not employment conditions and care home-level staffing factors have an impact on the quality of English care homes using a large, national data set of homes for the years 2016 to 2018. The study utilised appropriate statistical methods, including use of longitudinal data to tackle omitted variables and addressing both missing data and the potentially endogenous relationship between wages and care home quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…136 However, there is only a small amount of evidence for England as to the effects that staff and their employment conditions have on the quality of care homes. 148,149 This study sought to assess whether or not employment conditions and care home-level staffing factors have an impact on the quality of English care homes using a large, national data set of homes for the years 2016 to 2018. The study utilised appropriate statistical methods, including use of longitudinal data to tackle omitted variables and addressing both missing data and the potentially endogenous relationship between wages and care home quality.…”
Section: Discussionmentioning
confidence: 99%
“…141,146,147 Much of this literature is US based and focuses on clinical markers of quality or other process measures, not on final outcomes or quality of life. Previous analyses of care homes in England found that quality had a significant positive relationship with staff retention and a significant negative relationship with job vacancies 148 and that a lack of staff could lead to closure. 149 However, there is very little statistical evidence in England linking wages and training levels to care quality outcomes.…”
Section: Staff and Quality Of Carementioning
confidence: 95%
“…The majority of social care workers are female (80 per cent), with a mean age of about 43, having a low level of formal qualifications, and a growing number are migrants (Gardiner and Hussein 2015). However, despite the increase in employment, care providers are reporting high turnover (27 per cent) and vacancy rates (7 per cent), providing an important challenge to the provision of good quality services (Allan and Vadean 2020; Skills for Care 2016b).…”
Section: The Long‐term Care Workforcementioning
confidence: 99%
“…Therefore, care providers lacked the flexibility of passing cost increases on to charged fees, and changes to minimum wage legislation were expected to have a noticeable impact on the sector. The main concerns were that the increase in minimum wage will have a negative effect on employment, wage distribution, wage differentials, promotion prospects, employment conditions, quality of care, market sustainability, and/or noncompliance with minimum wage regulation (Allan and Vadean 2020; Gardiner 2015a,b; Gardiner, Hussein 2015; Low Pay Commission 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, alongside the complex needs of residents, the care home sector is characterised by high workloads, high rates of staff turnover, and difficulty in recruiting and retaining competent staff [ 1 , 13 ]. These issues challenge efforts to introduce and embed quality improvement (QI) and positive safety practices within care home organisational culture [ 14 ].…”
Section: Introductionmentioning
confidence: 99%